The Influence of Transformational Leadership on Employees Performance with Knowledge Sharing and Affective Commitment as Moderation - Didik Firmansyah; Dian Alfia Purwandari (Budapest International Research and Critics University, 2022)
In an organization, the human aspect is essential in determining success in achieving the organization's vision, mission, and goals. The role of humans in the organization is as a pillar and pillar of organizational success. Recognizing the importance of human resources for the survival and progress of the company, the company must have measures to encourage optimal employee performance and be able to meet the critical performance index that has been established. Several factors need to be considered to support employee performance, including transformational leadership: knowledge sharing, and affective commitment. The study was conducted on 194 employees of manufacturing companies in Indonesia, where the study was a quantitative study by spreading questionnaires and using Linkert scales as measurements and analyzed using Structural Equation Modeling (SEM). The results showed that transformational leadership is positively related to Knowledge Sharing, Affective Commitment, while knowledge sharing and affective commitment are positively related to employee performance. Transformational leadership is not positively related to employee performance. Furthermore, knowledge-sharing mediation and affective commitment can mediate Transformational Leadership relationships to employee performance.